Informaatiosektorin kasvihuonekaasupäästöt toimitusketjuissa - Natalia Kuosmanen; Timo O. Seppäläinen; Ilkka Ylhäinen (The Research Institute of the Finnish Economy (ETLA), 2022)
The environmental benefits and harms of information and communication technology (ICT) have been widely discussed in Finland since 2019. The climate impact of information and communication technology on the environment consists of three channels: procurement, the ICT sector's own carbon footprint, and the impact on other sectors of the economy (incl. public sector). Indeed, focusing solely on one sector's own emissions often leads to misleading conclusions about the industry's carbon footprint. This study examines the evolution of greenhouse gas emissions in the ICT sector and its supply chains in 2008-2019. In addition, the study examines the countries from which greenhouse gas emissions in the ICT sector and its supply chain originate.
Keywords: L8; L82; L86; L94; 330; Information economy sector; Supply chain; Greenhouse gas emissions; Carbon neutrality